2020
DOI: 10.1111/tbed.13669
|View full text |Cite
|
Sign up to set email alerts
|

Probe‐based real‐time reverse transcription loop‐mediated isothermal amplification (RRT‐LAMP) assay for rapid and specific detection of foot‐and‐mouth disease virus

Abstract: Foot-and-mouth disease (FMD) is a highly contagious transboundary disease of domestic and wild cloven-hoofed animals. FMD is associated with considerable economic losses due to decreased animal productivity and disease-associated restrictions on international trade in animal and animal products (Jamal & Belsham, 2013; World Organisation for Animal Heath (OIE), 2017). FMD virus (FMDV) belongs to the genus Aphthovirus within the family Picornaviridae and has been classified into seven genetically and immunologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Kubota et al developed the assimilating probe-based LAMP and subsequently designed a simple, low-power, portable handheld device to enable real-time detection of the LAMP amplicons [41,51]. This assay was mainly used for singleplex detection of viruses, and the sensitivities of this assay in the detection of foot-and-mouth disease virus (FMDV) and porcine circovirus 3 (PCV3) were 10 2 copies per µL and 50 copies per reaction, respectively [52,53].…”
Section: Applications Of the Probe-based Lamp Methods In Pathogen Det...mentioning
confidence: 99%
“…Kubota et al developed the assimilating probe-based LAMP and subsequently designed a simple, low-power, portable handheld device to enable real-time detection of the LAMP amplicons [41,51]. This assay was mainly used for singleplex detection of viruses, and the sensitivities of this assay in the detection of foot-and-mouth disease virus (FMDV) and porcine circovirus 3 (PCV3) were 10 2 copies per µL and 50 copies per reaction, respectively [52,53].…”
Section: Applications Of the Probe-based Lamp Methods In Pathogen Det...mentioning
confidence: 99%
“…To date, several reverse transcription LAMP (RT-LAMP) assays have been developed that are capable of detecting all seven FMDV serotypes and serotype-specific detection of O, A, C and Asia 1 FMDVs ( Lim et al, 2020 ). Timely diagnosis is essential for the control, monitoring and eradication of FMD.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…They found that lyophilization greatly improved the storage stability of test reagents without jeopardizing the assays' performance, which further supported the potential on field diagnosis of RT-LAMP assay ( Howson et al, 2017a ). Recently, Lim et al developed a probe-based real-time reverse transcription loop-mediated isothermal amplification (RRT-LAMP) assay for rapid and specific detection of FMDV, and the detection limit of the assay was 10 2 copies/μL which is comparable to that achieved by qRT-PCR ( Lim et al, 2020 ). Rapid and accurate detection of SVA is necessary to confirm the disease causing agent, and to initiate the implementation of control processes.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developed test identified all 7 FMDV serotypes while having no cross-reactivity with other tested viruses. In diagnostic samples, RT-LAMP assay had 97.1% agreement with gold-standard RT-qPCR as well [ 79 ]. There were other FMDV RT-LAMP assays designed to identify serotypes circulating in Korea [ 78 ], India [ 80 ], and Middle East [ 81 ].…”
Section: Ruminant Viral Diseases and Lamp Assays For Diagnosismentioning
confidence: 99%